GIS-based land suitability analysis for potential urban development sites in Diffun, Quirino - Sia, Edric Emmanuel A.; Villajuan, Jose Dan (Quezon City College of Architecture, University of the Philippines Diliman, 2020)
As the world moves towards urbanization, the demand for land for urban land use increases. If left unmanaged, this might result to the wastage of land that could have been used for more productive purposes, such as agriculture. Other developments can also pose risks to the environment and to those who inhabit it. Therefore, land suitability analyses must be done before moving on to urban planning. This study aims to create an urban suitability analysis of the municipality of Diffun in order to provide information for future urban planning. Considering that the revision of their Comprehensive Land Use Plan (CLUP) will start on 2021, it is indeed very timely to conduct this analysis. In this study, two methods of doing the analysis were integrated: Boolean overlay and weighted overlay. Using spatial data gathered, a total of 18 factors and restrictions were produced for the analysis. Restriction layers used in the Boolean overlay method included the following: existing built-up areas, erosion risk, flooding susceptibility, protected agricultural lands, other protected lands, Quirino Protected Landscape (QPL), slope, waterway buffers, and ecotourism site buffers. Meanwhile, the following were used as factors for the weighted overlay analysis: elevation, land-use type, distance to ecotourism sites, distance to local roads, distance to national and provincial roads, proximity to the población, distance to protected agricultural lands, distance to waterways, and slope. The weights of the factors were then calculated using the Analytic Hierarchy Process (AHP). It was found out in the study that only 0.32% of the total land area of the municipality is most suitable for urban land-use, while 87.36% is considered not suitable for the development of built-up areas.
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman
Keywords: Sustainable architecture -- Diffun (Quirino).; Urban development -- Diffun (Quirino).